Hierarchical α‐MnO2 Tube‐on‐Tube Arrays with Superior, Structure‐Dependent Pseudocapacitor Performance Synthesized via a Selective Dissolution and Coherent Growth Mechanism. Issue 8 (12th February 2016) - Yu, Bao Zhi; Dan Zhao, Xiao; Luo, Jun; Zhang, Hui Gang; Zhu, Yan Wu; Jing, Guang Yin; Ma, Pei; Ren, Zhao Yu; Fan, Hai Ming
Abstract : Hierarchical α‐MnO2 tube‐on‐tube arrays (HMNTAs) are controllably synthesized by a facile hydrothermal route. HMNTAs are comprised of single‐crystal [001]‐oriented tetragonal nanotubes, where the branch nanotubes are assembled onto a backbone nanotube along a specific crystallographic direction, showing a unique edge‐to‐edge structure. Time‐dependent evolution of the morphology reveals that the formation of HMNTAs undergoes a selective dissolution of δ‐MnO2 nanoflakes and a coherent growth of α‐MnO2 nanotubes. Additionally, the spatial structure of HMNTAs can be easily controlled from 4‐fold‐symmetry to 2‐fold‐symmetry by varying the diameter of branch nanotubes from 80 to 180 nm. Owing to remarkable structural features, the 4‐fold‐symmetry HMNTAs exhibit a specific capacitance of 780 F g −1 at 1 A g −1 and 98% capacitance retention after 5000 cycles at 10 A g −1, which is superior to that of 2‐fold‐symmetry HMNTAs and α‐MnO2 nanotube arrays. Furthermore, the prototype symmetric supercapacitor (SSC) device based on 4‐fold‐symmetry HMNTAs electrode exhibits high specific capacitance (213 F g −1 ), higher than that of the SSCs for 2‐fold‐symmetry HMNTAs (182 F g −1 ) and α‐MnO2 nanotube arrays (80 F g −1 ). This work demonstrates a previously undescribed level of structural and functional complexity in hierarchical nanoarrays and brings new perspectives on designing novel hierarchical nanoarrays for various structure‐sensitive applications. Abstract : Hierarchical α‐MnO2 tube‐on‐tube arrays (HMNTAs) are prepared via selective dissolution and coherent growth mechanism under hydrothermal conditions. The spatial structure of HMNTAs can be easily controlled from 4‐fold‐symmetry to 2‐fold‐symmetry. The 4‐fold‐symmetry HMNTAs exhibit better supercapacitor performance than 2‐fold‐symmetry HMNTAs and α‐MnO2 nanotube arrays.